Do We Have a Place for Non-Steroidal Anti-Inflammatory Drugs in Corneal Refractive Surgery? - N. V. Maychuk; I. A. Mushkova; M. R. Obraztsova (Oftalʹmologiâ, 2021)
Relevance. Corneal refractive surgery is a modern, dynamically developing segment of ophthalmology that provides highly predictable, safe and stable refractive results in patients with a wide range of ametropias. Corneal refractive surgery, usually is chosen by patients who lead an active lifestyle and need rapid medical and social rehabilitation, people with high requirements for the quality of life and showing increased expectations for the result of correction. Perhaps this is due to the fact that, according to a survey at the exit of the Department of refractive laser Surgery of the S.N. Fyodorov Eye Microsurgery Federal State Institution of the Russian Ministry of Health, Moscow, conducted after consulting a surgeon with a description of the course of the operation and the postoperative course, about 1 % of patients refuse surgery, fearing painful sensations in the postoperative period, and 23.4 % of the expected postoperative discomfort causes strong concerns.Purpose. To study the clinical efficacy and safety of Broxinac (0.09 % bromfenac solution) in the early postoperative period of corneal refractive surgery.Materials and methods. The study included 168 patients (168 eyes) with moderate and high myopia after PRK (24 eyes), FemtoLASIK (78 eyes) and ReLEx SMILE (66 eyes), divided into equal subgroups: in the main group, Broxinac was instilled once 30 minutes after the operation, and in the control group — placebo. In the PRK subgroup of the main group, daily instillations of Broxinac were continued until complete reepithelization. The severity of the indicators “eye pain”, “photophobia”, “lacrimation”, “foreign body sensation” was evaluated on a five-point scale, the state of the corneal epithelium when stained with fluorescein, and overall satisfaction with the operation.Results and discussion. It is established that the analgesic effect occurred on average after 4.4 ± 0.6 minutes. Broxinac had a rapid, pronounced analgesic effect in patients in the early postoperative period after keratorefractive surgery, without slowing of corneal reepithelization, and can be recommended for use in clinical practice for analgesia and relief of aseptic inflammatory reaction in the early postoperative period after FemtoLASIK and PRK. The ReLEx SMILE does not require pain relief.Conclusion. Analgesia of the early postoperative period increases patient satisfaction with the result of the operation, popularizes it and helps to attract patients who previously refused surgical correction of ametropia due to fear of painful sensations.